Supported metal catalyst for thermo-oxidative degradation of polyester plastics as well as preparation method and application of supported metal catalyst

By uniformly dispersing metal nanoparticles or single atoms on the silicon-aluminum molecular sieve, the problems of high energy consumption and high catalyst cost in the thermal oxygen degradation process of plastic waste are solved, and the efficient and low-cost polyester plastic degradation effect is achieved.

CN119746921AActive Publication Date: 2025-04-04UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202411944979.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, high safety risks and high catalyst costs in the thermal oxygen degradation process of plastic waste, making it difficult to achieve efficient and low-cost resource utilization.

Method used

A supported metal catalyst is used to uniformly disperse metal nanoparticles or single atoms by electrostatic adsorption and ion exchange method on silicon-aluminum molecular sieve to prepare a catalyst with high activity, good selectivity and strong stability.

Benefits of technology

It realizes efficient thermal oxygen degradation of polyester plastics, reduces energy consumption and safety risks, and has simple catalyst preparation method, low cost, and excellent catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746921A_ABST
    Figure CN119746921A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and particularly relates to a supported metal catalyst for thermal oxidative degradation of polyester plastics as well as a preparation method and application of the supported metal catalyst. The supported metal catalyst provided by the invention is prepared by the following steps: a) dipping a silicon-aluminum molecular sieve in a metal salt aqueous solution under a stirring condition; after the impregnation is finished, centrifuging and collecting a solid-phase product to obtain a catalyst precursor; in the step a), the silicon-aluminum molecular sieve is one or more of a ZSM molecular sieve, a USY molecular sieve, an LSP molecular sieve and a TS-1 molecular sieve; the metal salt is one or more of nickel salt, copper salt, cobalt salt and iron salt; the dipping temperature is 20-100 DEG C; and b) calcining the catalyst precursor under an aerobic condition to obtain the supported metal catalyst. The supported metal catalyst provided by the invention is simple in preparation process and low in cost, and has relatively high activity, selectivity and stability in solvent-free thermal oxidation degradation reaction of polyester plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a supported metal catalyst for thermal oxidation degradation of polyester plastics, and a preparation method and application thereof. Background Art

[0002] With the rapid development of human society, white pollution caused by discarded plastics has become a major problem in global environmental governance. On the other hand, plastic waste is one of the underdeveloped carbon resources. Therefore, recycling and reusing the existing large amount of plastic waste can not only alleviate future environmental pressure, but also optimize the energy structure and realize the transformation from fossil energy to renewable energy. Polyethylene terephthalate (PET) is the fourth largest source of plastic waste. However, due to factors such as low monomer recovery rate, difficult purification, expensive catalysts, and secondary pollution of solvents, PET and most other wastes are still recycled through mechanical technologies such as crushing, extrusion, and recycling.

[0003] By catalytically degrading plastic waste and recycling it and converting it into high-value chemicals such as monomers and fuels, it can not only effectively reduce the negative impact of plastics on the environment, but also promote the recycling of carbon resources. Thermal catalysis is a common method for valorizing plastic waste, without the need for additional separation or pretreatment of mixed polymer waste, but the conversion process requires harsh reaction conditions, high energy consumption and safety risks. At present, the adjustable acidity and unique pore structure in molecular sieve catalysts can improve the selectivity of plastic degradation products. Loading metals on molecular sieves can further enhance the activity of degradation reactions and further increase the degradation rate. In order to achieve sustainable development under the background of the dual carbon strategy, it is urgent to design and develop efficient, low-cost, thermally stable and highly active catalysts to realize the resource utilization of waste plastics. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a supported metal catalyst for thermal oxidation degradation of polyester plastics, and a preparation method and application thereof. The supported metal catalyst provided by the present invention has a simple preparation process, low cost, and has high activity, selectivity and stability.

[0005] The present invention provides a method for preparing a supported metal catalyst for thermal oxidation degradation of polyester plastics, comprising the following steps:

[0006] a) impregnating the silicon-aluminum molecular sieve in a metal salt aqueous solution under stirring conditions; after the impregnation is completed, collecting the solid phase product by centrifugation to obtain a catalyst precursor;

[0007] In step a), the silicon-aluminum molecular sieve is one or more of ZSM molecular sieve, USY molecular sieve, LSP molecular sieve and TS-1 molecular sieve; the metal salt is one or more of nickel salt, copper salt, cobalt salt and iron salt; the impregnation temperature is 20-100° C.;

[0008] b) calcining the catalyst precursor under oxygen conditions to obtain a supported metal catalyst.

[0009] Preferably, in step a), the concentration of the metal salt in the metal salt aqueous solution is 0.006-0.1 mol / L; the usage ratio of the metal salt aqueous solution to the silica-alumina molecular sieve is 50 mL: (0.5-1.5) g.

[0010] Preferably, in step a), the immersion time is 3 to 10 hours.

[0011] Preferably, in step a), the stirring speed is 400-1000 rpm.

[0012] Preferably, in step a), the centrifugal speed is 6000-12000 rpm, and the time is 2-10 min.

[0013] Preferably, in step a), the collected solid phase product is washed and dried.

[0014] Preferably, in step b), the calcination temperature is 300-800° C. and the calcination time is 2-6 hours.

[0015] The invention provides a supported metal catalyst for thermal oxidation degradation of polyester plastics, which is prepared according to the preparation method described in the above technical scheme.

[0016] The present invention provides a method for thermal oxidation catalytic degradation of polyester plastics, comprising the following steps:

[0017] In the presence of the supported metal catalyst described in the above technical solution and under aerobic conditions, the polyester plastic is heated and degraded to obtain a degradation product.

[0018] Preferably, the temperature of the heating degradation is 210-300° C., and the time is 1-100 h.

[0019] Compared with the prior art, the present invention provides a supported metal catalyst for thermal oxidation degradation of polyester plastics, and a preparation method and application thereof. The supported metal catalyst provided by the present invention is prepared according to the following steps: a) Under stirring conditions, the silicon aluminum molecular sieve is impregnated in a metal salt aqueous solution; after the impregnation, the solid phase product is collected by centrifugation to obtain a catalyst precursor; in step a), the silicon aluminum molecular sieve is one or more of ZSM molecular sieve, USY molecular sieve, LSP molecular sieve and TS-1 molecular sieve; the metal salt is one or more of nickel salt, copper salt, cobalt salt and iron salt; the impregnation temperature is 20-100°C; b) the catalyst precursor is calcined under aerobic conditions to obtain a supported metal catalyst. The supported metal catalyst provided by the present invention has simple preparation steps, mild preparation conditions and low preparation cost; during the preparation process, the catalyst uses electrostatic adsorption and ion exchange methods to evenly disperse the metal in the form of nanoparticles or single atoms on the silicon-aluminum molecular sieve carrier, achieving highly dispersed active sites and significantly improving the reaction activity of the catalyst; and, because the catalyst has a special and stable coordination environment, as well as the synergistic effect between the activity of the supported non-precious metal and the acidity of the molecular sieve carrier, it has the advantages of high reaction activity, good selectivity, and strong stability in the selective catalytic oxidation degradation reaction of plastics. In short, the supported metal catalyst provided by the present invention not only has a simple preparation method and low preparation cost, but also has excellent catalytic performance and high product selectivity when used as a catalyst for the oxidation degradation reaction of polyester plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 X-ray diffraction patterns of the catalysts of Examples 1 to 2 provided by the present invention;

[0022] Figure 2 Transmission electron microscope images of the catalysts of Examples 1 and 2 provided by the present invention;

[0023] Figure 3 This is a graph showing the yield of the target product terephthalic acid when the catalyst of Example 1 provided by the present invention is reused. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides a method for preparing a supported metal catalyst for thermal oxidation degradation of polyester plastics, comprising the following steps:

[0026] a) impregnating the silicon-aluminum molecular sieve in a metal salt aqueous solution under stirring conditions; after the impregnation is completed, collecting the solid phase product by centrifugation to obtain a catalyst precursor;

[0027] b) The catalyst precursor is calcined under oxygen conditions to obtain a supported metal catalyst for thermal oxidation degradation of polyester plastics.

[0028] In the preparation method provided by the present invention, in step a), the silicon aluminum molecular sieve is one or more of ZSM molecular sieve, USY molecular sieve, LSP molecular sieve and TS-1 molecular sieve, wherein the ZSM molecular sieve is preferably H-type ZSM-5 molecular sieve, more preferably NH4 + The H-type ZSM-5 molecular sieve after exchange; the silicon-aluminum ratio of the silicon-aluminum molecular sieve is preferably 30-200, specifically 60-75 or 130-150.

[0029] In the preparation method provided by the present invention, in step a), the metal salt is one or more of nickel salt, copper salt, cobalt salt and iron salt; the anion of the metal salt is preferably nitrate; the concentration of the metal salt in the metal salt aqueous solution is preferably 0.006-0.1 mol / L, specifically 0.006 mol / L, 0.008 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L.

[0030] In the preparation method provided by the present invention, in step a), the usage ratio of the metal salt aqueous solution to the silica-alumina molecular sieve is 50mL:(0.5-1.5)g, specifically 50mL:0.5g, 50mL:0.55g, 50mL:0.6g, 50mL:0.65g, 50mL:0.7g, 50mL:0.75g, 50mL:0.8g, 50mL:0.85g, 50mL:0.9g, 50mL:0.95g, 50mL:1g, 50mL:1.05g, 50mL:1.1g, 50mL:1.15g, 50mL:1.2g, 50mL:1.25g, 50mL:1.3g, 50mL:1.35g, 50mL:1.4g, 50mL:1.45g or 50mL:1.5g.

[0031] In the preparation method provided by the present invention, in step a), the immersion temperature is 20-100°C, specifically 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C; the immersion time is preferably 3-10h, specifically 3h, 4h, 5h, 6h or 7h. In the present invention, highly dispersed metal single atoms (M SA ) loaded with silicon-alumina molecular sieve catalyst; metal particles (M NP ) loaded with silicon-aluminum molecular sieve catalyst. In the present invention, the impregnation reaction temperature and time affect the metal loading form and coordination environment, and further affect the plastic thermal oxidation catalytic degradation activity of the catalyst product.

[0032] In the preparation method provided by the present invention, in step a), the stirring speed is preferably 400-1000 rpm, specifically 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm or 1000 rpm. In the present invention, the stirring treatment can improve the divergence and stability of the metal, thereby affecting the plastic thermal oxidation catalytic degradation activity of the catalyst product.

[0033] In the preparation method provided by the present invention, in step a), the centrifugal speed is preferably 6000-12000rpm, specifically 6000rpm, 6500rpm, 7000rpm, 7500rpm, 8000rpm, 8500rpm, 9000rpm, 9500rpm, 10000rpm, 10500rpm, 11000rpm, 11500rpm or 12000rpm; the centrifugal time is preferably 2-10min, specifically 2min, 2.5min, 3min, 3.5min, 4min, 4.5min, 5min, 5.5min, 6min, 6.5min, 7min, 7.5min, 8min, 8.5min, 9min, 9.5min or 10min. In the present invention, the centrifugal step affects the divergence and loading of the metal, and thus affects the plastic thermal oxidation catalytic degradation activity of the catalyst product.

[0034] In the preparation method provided by the present invention, in step a), the collected solid phase product is preferably washed and dried. The purpose of the washing is to remove excess ions on the solid phase product; the washing method is preferably water washing and / or alcohol washing; the drying method is preferably drying; the drying temperature is preferably 60 to 80°C, specifically 60°C, 65°C, 70°C, 75°C or 80°C; the drying time is preferably 5 to 20 hours, specifically 5 hours, 10 hours, 15 hours or 20 hours.

[0035] In the preparation method provided by the present invention, in step b), the aerobic condition is preferably a pure oxygen atmosphere or an air atmosphere.

[0036] In the preparation method provided by the present invention, in step b), the calcination temperature is preferably 300-800°C, more preferably 350-600°C, and specifically 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C; the calcination time is preferably 2-6h, specifically 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h. In the present invention, the calcination heat treatment affects the type and quantity of the catalyst oxygen species, and thus affects the thermal oxidation catalytic activity of the catalyst.

[0037] The present invention also provides a supported metal catalyst for thermal oxidation degradation of polyester plastics, which is prepared according to the preparation method described in the above technical scheme. In the present invention, the metal loading of the supported metal catalyst is preferably 0.02-2wt% calculated by inductively coupled plasma testing, and can be specifically 0.02wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%.

[0038] The present invention also provides a method for thermal oxidation catalytic degradation of polyester plastics, comprising the following steps:

[0039] In the presence of the supported metal catalyst described in the above technical solution and under aerobic conditions, the polyester plastic is heated and degraded to obtain a degradation product.

[0040] In the method for thermal oxidation catalytic degradation of polyester plastics provided by the present invention, the polyester plastics include but are not limited to polyethylene terephthalate; the polyester plastics are preferably in the form of fragments or powders.

[0041] In the method for thermal oxidation catalytic degradation of polyester plastics provided by the present invention, the aerobic condition is preferably a pure oxygen atmosphere or an air atmosphere.

[0042] In the method for thermal oxidation catalytic degradation of polyester plastics provided by the present invention, the temperature of the heating degradation is preferably 210-300°C, specifically 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C or 300°C; the time of the heating degradation is preferably 1-100h, specifically 1h, 5h, 10h, 20h, 50h, 70h or 100h.

[0043] The supported metal catalyst provided by the technical solution of the present invention is mainly through electrostatic adsorption, supplemented by ion exchange method, so that the non-precious metal iron is evenly dispersed on the silica-alumina molecular sieve carrier in the form of single atoms, which is not easy to aggregate into particles in large quantities, and has high reaction activity. Due to the special and stable coordination environment and the synergistic effect between the loaded non-precious metal single atoms and the acidic sites of the silica-alumina molecular sieve, the catalyst has the advantages of high activity, good selectivity, strong stability, etc. In the oxidative degradation reaction of polyester plastics, the catalyst of the silica-alumina molecular sieve loaded metal provided by the technical solution of the present invention has excellent catalytic performance. In short, the supported metal catalyst provided by the technical solution of the present invention not only has high activity, high selectivity and high stability, but also has a simple preparation method and low preparation cost, and can show excellent catalytic performance in the oxidative degradation reaction of polyester plastics.

[0044] For the purpose of greater clarity, the invention is described in detail through the following examples.

[0045] Example 1

[0046] A ZSM-5 molecular sieve supported iron catalyst is prepared by the following steps:

[0047] 50 mL of 0.06 M Fe(NO)3·xH2O and 1 g of NH4 with a silicon-aluminum ratio of 130-150 + The exchanged H-type ZSM-5 was mixed uniformly, stirred and impregnated at 60°C and 600 rpm for 6 hours, then cooled to room temperature, and then centrifuged at 10,000 rpm for 5 minutes. The product was then washed with deionized water to remove nitrate ions, then washed with alcohol, and dried at 80°C to obtain a catalyst precursor.

[0048] The catalyst precursor obtained by drying was placed in a muffle furnace and calcined at 550°C for 3 h in an air atmosphere, and then cooled to room temperature to obtain a silicon-aluminum molecular sieve catalyst mainly loaded with iron single atoms, named Fe SA / ZSM.

[0049] Specifically, during the implementation of Example 1 of the present invention, the following test results were obtained:

[0050] (1) X-ray diffraction was used to analyze the Fe SA / ZSM was characterized, and the results are shown in Figure 1 .Depend on Figure 1 The results show that the Fe SA There is no obvious diffraction peak of iron species in the / ZSM catalyst, which proves that it is a single iron atom.

[0051] (2) The Fe prepared in Example 1 was examined by transmission electron microscopy. SA / ZSM observation, the results are shown in the upper left and upper right figures of Figure 2, Figure 2 The upper left picture is a transmission electron microscope image of FeSA / ZSM, and the upper right picture is a distribution diagram of iron elements in the transmission electron microscope test of FeSA / ZSM. Figure 2 The results show that the Fe SA / ZSM catalyst has single iron atoms uniformly dispersed on the ZSM-5 support.

[0052] (3) The Fe prepared in Example 1 SA / ZSM catalyst is used as a catalyst for the oxidation degradation reaction of PET plastic and its performance is tested. The specific process is as follows:

[0053] PET oxidative degradation process, 50mg PET powder (50μm, M w : 20000~200000), 30 mg of the catalyst prepared in Example 1 of the present invention is added to the reactor, and pure oxygen at normal pressure is introduced by means of air bags, balloons or gas cylinders. Set the reaction temperature and time, and cool to room temperature after the reaction is completed. The reactor should have a condensation part so that the sublimated solid product terephthalic acid can be fully condensed. After the reaction is completed, open the reactor and use a polar organic solvent such as dimethyl sulfoxide to dissolve the solid product terephthalic acid, and filter and separate it. The separated solid catalyst is washed and dried for reuse. The separated terephthalic acid product is analyzed by a nuclear magnetic resonance spectrometer to obtain the following: Figure 3 The product performance diagram shown in Figure 1 is Figure 3 It can be seen that the catalyst prepared in Example 1 of the present invention has a strong performance in oxidative degradation of polyester plastics. At a reaction temperature of 260° C. and pure oxygen conditions, with polyethylene terephthalate as the reaction substrate, it is resistant to oxidation and highly active to produce terephthalic acid with a selectivity greater than 99%, and there is no obvious attenuation after 6 cycles.

[0054] Example 2

[0055] The preparation process of the catalyst is the same as that of Example 1, except that the temperature during the impregnation of the metal salt solution and the silica-alumina molecular sieve is changed to 80°C, and a silica-alumina molecular sieve catalyst mainly loaded with iron nanoparticles is obtained, which is named Fe NP / ZSM.

[0056] During the implementation of Example 2 of the present invention, the following test results were obtained:

[0057] (1) X-ray diffraction was used to analyze the Fe NP / ZSM was characterized, and the results are shown in Figure 1 .Depend on Figure 1 The results show that the Fe NP / ZSM catalyst has no obvious metal diffraction peak of iron species.

[0058] (2) The Fe prepared in Example 2 was examined by transmission electron microscopy. NP / ZSM observation, the results are shown in the lower left and lower right figures of Figure 2, Figure 2 The lower left picture shows Fe NP Transmission electron microscope image of / ZSM, the lower right image is Fe NP / ZSM transmission electron microscope test of iron distribution map. Figure 2 The results show that the Fe NP / ZSM catalyst has iron nanoparticles dispersed on a ZSM-5 support.

[0059] (3) The Fe prepared in Example 2 NP / ZSM catalyst was used as a catalyst for PET plastic oxidation degradation reaction and performance testing was carried out. The specific process was the same as Example 1. The results showed that the plastic oxidation depolymerization reaction had high activity and selectivity greater than 99%.

[0060] Example 3

[0061] The preparation process of the catalyst is the same as that of Example 1, except that 50 mL of 0.03 M Fe(NO)3·xH2O and 1 g of NH4 with a silicon-aluminum ratio of 130-150 are used. + The exchanged H-type ZSM-5 is mixed uniformly.

[0062] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0063] Example 4

[0064] The preparation process of the catalyst was the same as that of Example 1, except that 40 mL of 0.06 M Fe(NO)3·xH2O and 1 g of NH4 with a silicon-aluminum ratio of 130 to 150 were used. + The exchanged H-type ZSM-5 is mixed uniformly.

[0065] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0066] Example 5

[0067] The preparation process of the catalyst is the same as that of Example 1, except that copper nitrate and iron nitrate are used alone or together as metal sources to be loaded on the silica-alumina molecular sieve.

[0068] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0069] Example 6

[0070] The preparation process of the catalyst is the same as that of Example 1, except that a layered pillared zeolite (LSP) type molecular sieve is used.

[0071] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0072] Example 7

[0073] The preparation process of the catalyst is the same as that of Example 1, except that a silicon-aluminum molecular sieve with a silicon-aluminum ratio of 60 to 75 is used.

[0074] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0075] Example 8

[0076] The preparation process of the catalyst is the same as that of Example 1, except that 1L of 0.06M Fe(NO)3·xH2O and 20g of NH4 with a silicon-aluminum ratio of 130-150 are used. + The exchanged H-type ZSM-5 is mixed uniformly.

[0077] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0078] Example 9

[0079] The preparation process of the catalyst is the same as that of Example 1, except that the stirring impregnation reaction is carried out at 70°C.

[0080] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0081] Example 10

[0082] The preparation process of the catalyst is the same as that of Example 1, except that the stirring impregnation reaction time is 5 h.

[0083] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0084] Embodiment 11

[0085] The preparation process of the catalyst was the same as that of Example 1, except that the stirring speed of the impregnation reaction was 800 rpm.

[0086] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0087] Example 12

[0088] The preparation process of the catalyst was the same as that of Example 1, except that the centrifugal speed was 8000 rpm and the time was 7 min.

[0089] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0090] Example 13

[0091] The preparation process of the catalyst was the same as that of Example 1, except that the drying temperature was set to 70° C. after stirring and centrifuging.

[0092] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0093] Embodiment 14

[0094] The preparation process of the catalyst is the same as that of Example 1, except that an oxygen atmosphere is used as the calcination oxidizing atmosphere.

[0095] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0096] Embodiment 15

[0097] The preparation process of the catalyst is the same as that of Example 1, except that the calcination temperature is 450° C. for 4 h.

[0098] The reaction performance test is the same as that in Example 1, and the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0099] Example 16

[0100] The preparation process and performance test method of the catalyst were the same as those in Example 1, except that the reaction substrate polyethylene terephthalate (PET) was replaced by polybutylene adipate (100 μm, M w :30000~200000). According to the test, the plastic oxidation depolymerization reaction has high activity and selectivity greater than 99%.

[0101] Embodiment 17

[0102] The preparation process and performance test method of the catalyst are the same as those in Example 1, except that during the thermal oxidation catalytic degradation of polyethylene terephthalate, atmospheric pressure air is introduced. According to the test, the plastic oxidative depolymerization reaction has high activity and selectivity greater than 99%.

[0103] In summary, the embodiments of the present invention not only have high activity, high selectivity and high stability, but also have a simple preparation method and low preparation cost, and can exhibit excellent catalytic performance in the oxidative degradation reaction of polyester plastics.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a supported metal catalyst for thermal oxidation degradation of polyester plastics, characterized in that: The following steps are involved: a) impregnating the silicon-aluminum molecular sieve in a metal salt aqueous solution under stirring; After the impregnation is completed, the solid phase product is collected by centrifugation to obtain a catalyst precursor; In step a), the silicon-aluminum molecular sieve is one or more of ZSM molecular sieve, USY molecular sieve, LSP molecular sieve and TS-1 molecular sieve; the metal salt is one or more of nickel salt, copper salt, cobalt salt and iron salt; the impregnation temperature is 20-100° C.; b) The catalyst precursor is calcined under oxygen conditions to obtain a supported metal catalyst for thermal oxidation degradation of polyester plastics.

2. The preparation method according to claim 1, characterized in that: In step a), the concentration of the metal salt in the metal salt aqueous solution is 0.006-0.1 mol / L; the usage ratio of the metal salt aqueous solution to the silica-alumina molecular sieve is 50 mL: (0.5-1.5) g.

3. The preparation method according to claim 1, characterized in that: In step a), the immersion time is 3 to 10 hours.

4. The preparation method according to claim 1, characterized in that: In step a), the stirring speed is 400-1000 rpm.

5. The preparation method according to claim 1, characterized in that: In step a), the centrifugal speed is 6000-12000 rpm and the time is 2-10 min.

6. The preparation method according to claim 1, characterized in that: In step a), the collected solid phase product is washed and dried.

7. The preparation method according to claim 1, characterized in that: In step b), the calcination temperature is 300-800° C. and the calcination time is 2-6 hours.

8. A supported metal catalyst for thermal oxidation degradation of polyester plastics, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. A method for thermal oxidation catalytic degradation of polyester plastics, characterized in that: The following steps are involved: In the presence of the supported metal catalyst as claimed in claim 8 and under aerobic conditions, the polyester plastic is thermally degraded to obtain a degradation product.

10. The method for thermal oxidation catalytic degradation of polyester plastics according to claim 9, characterized in that: The temperature of the heating degradation is 210-300° C., and the time is 1-100 hours.

Citation Information

Patent Citations

  • Supported metal oxide catalyst for catalytically degrading polyethylene glycol terephthalate and preparation method and use thereof

    CN109289900A

  • Iron monatomic catalyst, preparation and applications thereof

    CN111215127A

  • Method for preparing monatomic and nanocluster synergistically supported catalyst through atomic reconstruction

    CN114950412A

  • Asymmetric oxygen coordination transition metal monatomic catalyst as well as preparation method and application thereof

    CN116237085A

  • Composition and method for preparing the same

    US20240228421A1

Cited By

  • Plastic thermal oxidation degradation device heated by composite heat source and degradation process of plastic thermal oxidation degradation device

    CN121060940A